The Co-construction of Identity in a Village High School in the Philippines: Implication for the Implementation of Educational Development Programs - Fontejon-Bonior, Gina A. (Silliman Journal, 2023)
This article presents the conclusions and limitations of a critical ethnographic study on the experiences of apprenticeship and advancement of agency of secondary school students in a rural public school in the Philippines. Findings of the study show that well-intentioned educational programs for socio-economically disadvantaged communities could result in the further marginalization of students. This study discusses four factors that contribute to such marginalization: 1) the limited agency of students, teachers, administrators, and the school as a collective identity; 2) the silencing of critical voices; 3) the beliefs of teachers and other school authorities that students are created equal and attend school bringing with them the same amount of "social capital"; and 4) the educators' lack of awareness of the need for explicit instruction and apprenticeship on the secondary Discourses used in school. The article then suggests concrete means of addressing such concerns especially in the context of implementing educational development programs in socio-economically and culturally disadvantaged communities.